2021
DOI: 10.1001/jamanetworkopen.2020.33424
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Patient Protection and Affordable Care Act’s Increase in Fees for Primary Care and Access to Care for Dual-Eligible Beneficiaries

Abstract: IMPORTANCE The Patient Protection and Affordable Care Act (ACA) temporarily increased primary care practitioners' (PCP) Medicaid fees to that of Medicare for 2013 to 2014 (fee bump) to help accommodate potential increases in demand for care with ACA coverage expansion. This also increased fees for PCPs treating dual-eligible Medicare and Medicaid beneficiaries in many states and eliminated payment differentials for dual-eligible vs non-dual-eligible Medicare beneficiaries that could limit access to care. OBJEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(62 reference statements)
2
7
0
Order By: Relevance
“…8,22,23 However, our findings are consistent with a recent study by Fung and colleagues, which did not find any increase in office visits among duals due to the fee bump, either overall or in states with larger or more sustained payment increases. 13 Our findings also resonate with Chen and Lakdawalla, 25 who found that separate Medicare payment changes led to smaller changes in physician visits among low-income beneficiaries than those with higher incomes. Chen and Lakdawalla hypothesize that this more muted response reflects physicians' recognition that higher prices will result in higher out-of-pocket costs for individuals without supplemental insurance, and that these outof-pocket costs may be more burdensome to low-income patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…8,22,23 However, our findings are consistent with a recent study by Fung and colleagues, which did not find any increase in office visits among duals due to the fee bump, either overall or in states with larger or more sustained payment increases. 13 Our findings also resonate with Chen and Lakdawalla, 25 who found that separate Medicare payment changes led to smaller changes in physician visits among low-income beneficiaries than those with higher incomes. Chen and Lakdawalla hypothesize that this more muted response reflects physicians' recognition that higher prices will result in higher out-of-pocket costs for individuals without supplemental insurance, and that these outof-pocket costs may be more burdensome to low-income patients.…”
Section: Discussionsupporting
confidence: 87%
“…Our results differ from several prior studies which found positive supply elasticities ranging from 0.5 to 2 in response to Medicare price changes in the full Medicare population 8,22,23 . However, our findings are consistent with a recent study by Fung and colleagues, which did not find any increase in office visits among duals due to the fee bump, either overall or in states with larger or more sustained payment increases 13 . Our findings also resonate with Chen and Lakdawalla, 25 who found that separate Medicare payment changes led to smaller changes in physician visits among low‐income beneficiaries than those with higher incomes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Before the pandemic, Medicare beneficiaries with disabilities’, especially those who were dual eligible, access to care and the quality of care they receive were negatively impacted by the fragmented system through which they receive services (Cubanski & Neuman, 2010; Feng, 2018; Figueroa et al, 2018; Warshaw & DeGolia, 2015); this may contribute to why Medicare beneficiaries with disabilities did not get the counseling/therapy services they needed during the pandemic. In fact, some health care providers will not serve Medicare beneficiaries because of poor reimbursement rates (Cubanski & Neuman, 2010; Fung et al, 2021; Warshaw & DeGolia, 2015). Given lower income Medicare beneficiaries with disabilities in our study were more likely to not get the counseling/therapy they needed, we believe cost may have also been a factor in these disparities.…”
Section: Discussionmentioning
confidence: 99%
“…While food insecurity negatively harms the physical and mental health of everyone, 1 , 2 , 3 , 4 , 5 , 6 , 7 it may be particularly harmful for PWD who were Medicare beneficiaries who are already vulnerable, underserved, and have multiple chronic conditions. 26 , 27 , 33 , 34 , 35 , 36 , 37 A multipronged approach to food insecurity that addresses public health and other systems and structures, ranging from disability services to discrimination, is critical. 2 , 38 …”
Section: Discussionmentioning
confidence: 99%